Queering Disability. Homosexuality in residential facilities for people with mental disabilities - Sonja Dudek; Karin Jeschke; Ulrike Lehmkuhl (Disability Studies Quarterly, 2006)
This article discusses the subject of how homosexual behavior is dealt with in German residential facilities for people with cognitive disabilities. It is based on empirical data from a qualitative pilot study funded by the German Ministry for Family, Senior Citizens, Women and Youths. Although homosexuality was only a marginal topic of this study, it was frequently mentioned in interviews held with various care workers.[1] The passages of the interviews that deal with the residents' homosexual behavior, therefore, serve as the empirical basis for this exploratory research. Dudek, Jeschke and Lehmkuhl argue that there still is a knowledge deficit concerning homosexuality and cognitive disability in Germany, which can be observed both in theory and in practice. This article begins with a short overview of how cognitive disability and homosexuality are discussed in the special education literature. It then applies ideas and concepts from the field of queer theory to the subject. The empirical data is classified and analyzed in four subcategories: a) Homosexuality is treated as a taboo, b) Homosexuality is devalued, c) Homosexual residents are not supported and d) Homosexuality is not discriminated against. The last section of this article discusses the results of the study and provides ideas and recommendations for practice.
Keywords: People with cognitive disabilities; homosexuality and intellectual disability; care worker attitudes toward homosexuality